Precariety of basic sanitation and the presence of the african snail (Achatina Fulica Bowdich, 1822) in the city of Manaus / AM-Brasil - Souza, Michael Guimarães de; Lachi, Ana Mara Cruz; Albuquerque, Adoréa Rebello da Cunha (Revista Nacional de Gerenciamento de Cidades, 2020)
The African snail (Achatina fulica) represents a serious risk to public health as it is a vector of disease such as eosinophilic meningitis. This mollusk has become abundant in urban environments, where its habitat is the areas located around rivers and vacant lots. Due to this context, it was the main objective of the present research, the identification of the areas of occurrence of the African snail in face of the precarious situation of sanitation in Manaus. The methodology was worked through field surveys, georeferencing and use of the database of the Brazilian Institute of Geography and Statistics. The results show that in the 126 areas mapped with the presence of the African snail, 119 census tracts are marked by the existence of untreated sewage and inadequate destination. In these sectors, the highest population density of the species was noted. The precarious situation of sanitation in the capital of Amazonas, shows that only 12.3% of the population receives sewage collection service, and the scarcity of sewage services becomes the main factor in favoring the spread of African snails in Manaus.